Hábitos alimenticios y su relación con el estado nutricional en niños (as) de 5 a 7 años, de la Unidad Educativa Francisco Huerta Rendón, Babahoyo, Los Ríos mayo – septiembre 2019 - Gastezzi Aguilera, Lourdes De Las Mercedes (2019)
INTRODUCTION: Eating Habits are those that are acquired from the first years of life until the day of death, nowadays it is known that the first trigger of nutrition problems are caused by disorderly eating habits since we have adopted the common current changes, where food of natural origin is significantly replaced by industrialized. GENERAL OBJECTIVE: To establish the relationship between eating habits and nutritional status of children from 5 to 7 years of the Francisco Huerta Rendon de Babahoyo Educational Unit. METHODOLOGY: A descriptive, observational, correlational and explanatory investigation was proposed where students from 5 to 7 years of the Francisco Huerta Rendón Educational Unit in the province of Los Ríos worked, with the purpose of showing what are the habits food, were evaluated by anthropometric measures using the growth charts of the World Health Organization and surveys of parents. RESULTS: Regarding the assessment of nutritional status by BMI / AGE, it was found that the percentage of malnutrition is 11%, normal 17%, overweight 18%, obesity type I 19%, obesity type II 35%. CONCLUSIONS: In conclusion it was shown that eating habits and nutrition are closely related, thus meeting the objectives set.